Undergraduate student's perception on assessment experience in a Malaysian medical school: comparison among gender, ethnicity and phase of study - Adam, Siti Khadijah; Mazlan, Nur Atiqah; Selvakumar, Shivaprakash; Xian, Hui Teh; Idris, Faridah (IIUM Press, 2021)
It is a well-known fact that assessment influences learning and study behaviour. Assessment affects what and how students learn, either positive or negative learning behaviour. This study was aimed to determine students’ perceived assessment experience and the comparison among different gender, ethnicity, and phase of the study. MATERIALS AND METHODS: This is a cross-sectional study. Assessment Experience Questionnaire (AEQ) version 3.3 was distributed to 324 undergraduate medical students of Universiti Putra Malaysia. The AEQ score among different gender, ethnicity, and phase of the study was compared using independent t-test and one-way ANOVA. RESULTS: Female students were found to develop a surface approach to learning, learn new things from the assessment, and be satisfied more with the teaching compared to males. Chinese students tended to put higher effort into learning compared to Malay. Clinical students valued more the feedback received and had clearer goals and expectations for their work than preclinical students. However, preclinical students tended to put a higher quantity of effort, learn wider coverage of syllabus and develop a surface approach of learning than clinical students. The respondents commented that feedback is lacking and suggested having more feedback sessions with their teachers after assessment. CONCLUSION: There were different assessment experiences and learning found among different gender, race, and phase of the study. These may affect their academic performance and are probably due to the curriculum setting. Understanding student assessment experience and its impact helps the faculty to improve the assessment structure for a conducive assessment environment and meaningful learning experience for the students.